2010
DOI: 10.1016/j.bcp.2009.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of small molecule inhibitors of pyruvate kinase M2

Abstract: A common feature of tumors arising from diverse tissue types is a reliance on aerobic glycolysis for glucose metabolism. This metabolic difference between cancer cells and normal cells could be exploited for therapeutic benefit in patients. Cancer cells universally express the M2 isoform of the glycolytic enzyme pyruvate kinase (PKM2), and previous work has demonstrated that PKM2 expression is necessary for aerobic glycolysis and cell proliferation in vivo. Because most normal tissues express an isoform of pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
159
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(167 citation statements)
references
References 23 publications
5
159
0
Order By: Relevance
“…Although allosteric activation of enzyme activities by FBP is concentration dependent (Figure 3a), we used FBP (125 mM) for the enzyme assay. First, FBP (125 mM) significantly activated PKM2 (Figure 3a), so that the results of this study could be compared with the reported data (Vander Heiden et al, 2010). In fact, the IC 50 of compound-3 determined in this study is similar to the reported data.…”
Section: Pkm2 Is a Potential Target Of Shikoninsupporting
confidence: 84%
See 1 more Smart Citation
“…Although allosteric activation of enzyme activities by FBP is concentration dependent (Figure 3a), we used FBP (125 mM) for the enzyme assay. First, FBP (125 mM) significantly activated PKM2 (Figure 3a), so that the results of this study could be compared with the reported data (Vander Heiden et al, 2010). In fact, the IC 50 of compound-3 determined in this study is similar to the reported data.…”
Section: Pkm2 Is a Potential Target Of Shikoninsupporting
confidence: 84%
“…Shikonin and its enantiomeric alkannin are potent inhibitors of PKM2 but not PKM1 and PKL An enzyme assay was performed according to the reported method for identification of compound-3 (N-(3-carboxy-4-hydroxy)phenyl-2,5,-dimethylpyrrole) as PKM2 inhibitor, the most potent inhibitor discovered from a screening of over 100 000 compounds (Vander Heiden et al, 2010). Shikonin and alkannin (the optical isomer of shikonin) showed comparable inhibitory activities, more potent than other shikonin analogs (Figures 3b and c).…”
Section: Pkm2 Is a Potential Target Of Shikoninmentioning
confidence: 99%
“…Selection for a less active form of pyruvate kinase may help divert glucose metabolites upstream of pyruvate kinase into biosynthetic pathways 5,97,100 . Efforts have been made to selectively inhibit PKM2 101,102 . Peptide aptamers that promote the less active form of pyruvate kinase have been shown cause energy stress and cell death in cultured cancer cells 101 , and more modest effects were observed using small molecule inhibitors of PKM2 102 .…”
Section: --Deoxyglucose (2dg) Is An Inhibitor Of Glucose Metabolism mentioning
confidence: 99%
“…Efforts have been made to selectively inhibit PKM2 101,102 . Peptide aptamers that promote the less active form of pyruvate kinase have been shown cause energy stress and cell death in cultured cancer cells 101 , and more modest effects were observed using small molecule inhibitors of PKM2 102 . Targeting PKM2 with shRNA can slow cell proliferation in cell culture 99 , however these cells retain the ability to proliferate even with the near complete absence of pyruvate kinase activity.…”
Section: --Deoxyglucose (2dg) Is An Inhibitor Of Glucose Metabolism mentioning
confidence: 99%
“…The L gene is spliced to produce the L and R isoform (mainly expressed in liver and red blood cells respectively) while the M gene splices to form the M1 or M2 isoforms of pyruvate kinase. It has been reported that tumor cells overexpress PKM2 [10] .…”
Section: Introductionmentioning
confidence: 99%